Eksplorasi Implementasi Teknik Membatik Tulis dengan Canting Elektrik dan Teknik Colet untuk Siswa Jenjang SMP - Sekti Pratiwi; Indar Sabri; Djuli Djatirambudi; Anik Juwairiyah (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2025)
Batik is a cultural heritage of the Indonesian nation. Schools that can develop batik are very effective and have benefits for all groups. This is relevant to the Arts and Culture subject at the junior high school level. This study aims to introduce Batik to students as a step towards preserving Batik and teaching them that creating Batik is easy and can be done by junior high school students. This research is qualitative and uses the Design-Based Research (DBR) method to produce effective learning outcomes. Furthermore, this study applies the Design-Based Research (DBR) method with the Reeves model, which is oriented towards developing practice-based solutions in an educational context. This method is in line with the research and development (R&D) approach, which aims to create or refine products to better suit user needs. Conceptually, DBR emphasizes a practical process that includes problem identification, design, implementation, and systematic product evaluation. The results of the research on the development of techniques using electric canting and colet techniques provide convenience and effectiveness to junior high school students, thereby significantly improving their skills. Exploring the implementation of electric canting and the colet technique is easy and efficient for producing batik. Compared to conventional canting, it is efficient in terms of saving materials and tools, as well as saving time and effort. Another advantage is the ability to produce richer and more varied colors, including achieving color gradation, and serving as a branding tool for batik fabrics.